2022
DOI: 10.1039/d2ra00771a
|View full text |Cite
|
Sign up to set email alerts
|

A review on metal-doped chalcogenide films and their effect on various optoelectronic properties for different applications

Abstract: The schematic presentation of some metal-doped chalcogenide thin films.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(38 citation statements)
references
References 137 publications
(278 reference statements)
1
37
0
Order By: Relevance
“…However, their practical applications have been severely restricted by some inherent flaws and people’s never-ending pursuit for “perfection”. Therefore, the aggressive explorations of innovative NLO materials have aroused the curiosity of many academics. …”
mentioning
confidence: 99%
“…However, their practical applications have been severely restricted by some inherent flaws and people’s never-ending pursuit for “perfection”. Therefore, the aggressive explorations of innovative NLO materials have aroused the curiosity of many academics. …”
mentioning
confidence: 99%
“…Figure 7 plots the measured electrical resistivity ( ρ ) of In 2 (Te 0.98 Se 0.02 ) 3 thin films and confirms the semiconducting behavior of the materials [ 39 ]. The ρ curve seemed to be higher for irradiated samples than for pristine samples, revealing the influence of SHI irradiation, which modified the surface of the materials through the grain boundaries.…”
Section: Resultsmentioning
confidence: 66%
“…The multifunctional Bi 2 ZnOB 2 O 6 single crystal is used for the SHG/THG generation process, where it is observed that it shows 3.22 × 10 −21 m 2 V −2 thirdorder nonlinear susceptibility by taking silica as the calibrating material. 66 Such films shows a higher χ (3) value (7.20 × 10 −18 ) upon annealing at 475 K. In the study presented here, χ (3) varies 4.524 × 10 −11 to 14.146 × 10 −11 esu upon annealing at higher temperatures. This increase in nonlinear susceptibility upon annealing enables its application as a frequency converter, a logic element, etc.…”
Section: Nonlinear Optical Propertiesmentioning
confidence: 54%
“…3.4.1. Nonlinear Susceptibility [χ (3) ] and Nonlinear Refractive Index (n 2 ). For chalcogenide materials, nonlinearity is one of the important properties that covers a broad portion of the electromagnetic spectrum.…”
Section: Nonlinear Optical Propertiesmentioning
confidence: 99%